Prevalence of pathological skin-picking in dermatological patients - Spitzer, Carsten; Lübke, Laura; Lindstädt, Tereza; Gallinat, Christina; Tietze, Julia K.; Emmert, Steffen; Thiem, Alexander (Journal of psychiatric research, 2022)
Objective - The prevalence of pathological skin-picking (PSP) has predominantly been studied in students and the community, but not yet in dermatological patients. However, those may be at increased risk of PSP because it is often triggered by the feel or look of the skin. Thus, its prevalence among patients with a physician-diagnosed dermatological disease remains to be determined. - Methods - A consecutive series of 460 adult patients attending a dermatological university outpatient clinic was administered the 8-item Skin Picking Scale-Revised (SPS-R). They also reported demographic data and rated the severity of their skin disease. The dermatologist evaluating the patient provided his/her diagnosis. - Results - PSP as defined by SPS-R scores ≥7 was reported by 121 participants (26.3%). It was significantly more frequent in patients with atopic dermatitis (AD, OR = 3.23; 95% CI: 1.95-5.68) and psoriasis (OR = 1.64; 95% CI: 1.00-2.67), but less frequent in those with malignant epithelial skin tumors (OR = 0.10; 95% CI: 0.02-0.43). PSP was not associated with female gender or younger age. - Conclusions - Our findings indicate that PSP affects about one in four patients with skin disease. In particular, individuals suffering from atopic dermatitis may represent a high-risk population for PSP deserving early recognition and adequate treatment.
Published online: 15 January 2022
Gesehen am 06.07.2022